Invasive mole presenting as acute abdomen - Mondal, Suresh Chandra; Pal, Sudip Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We reporting this case as acute abdomen and admitted into the surgical ward. The patient was in shock due to hemoperitonium and emergency laparotomy done and found that it was a perforating molar pregnancy. Total hysterectomy done, five units blood transfusion done. β hCG levels regress quickly and spontaneously.